Manipulatives and semiotic tools of Game of Go as playful and creative activity to learn mathematics in early grades in France - Cabassut, Richard; Fenech, Antoine (Teaching Mathematics and Computer Science, 2020)
This research develops resources to teach mathematics in French primary school by using the game of Go. A group of searchers, teachers and go players meet at university to produce teaching resources. These resources are implemented in the classroom. Then the group evaluate this implementation and improve the resources. The aim of this classroom research is to study the opportunities of the game of Go to learn mathematics and to propose a teacher training course to implement the game of Go in French primary schools in accordance with the French syllabus. Game of Go appears as a manipulative and semiotic tool to learn mathematics at primary school. Subject Classification: 97D50, 97U60